Respect : delivering results by giving employees what they really want - Wiley, Jack, 1952- (Jossey-Bass, 2012)
"A properly conceived employee survey program represents an opportunity to impact and strengthen the organization, making it more competitive in the marketplace in which it operates. Creating Motivated Workforces offers best practices by identifying the industries and job types that best deliver what employees want. It also guides organizations in the most effective survey feedback and action planning processes. Based on twenty-five years of data, the book provides targeted and practical recommendations for how organizations, leaders, and managers can better build more engaged and committed workforces"--